PSIKOLOGI DALAM DUNIA PENDIDIKAN - Ni Luh Drajati Ekaningtyas (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to scientifically examine the role of psychology in education or widely known as educational psychology. This study uses a literature study to find out about the meaning, scope, objectives, benefits, and application of educational psychology. The results of the analysis illustrate that educational psychology is a branch or sub-discipline of psychology that specializes in how to understand teaching and learning in an educational environment. The understanding of teaching and learning can be the basis for educators and education managers in recognizing the potential of students and environmental condotions that affect them. This basis can be used as a reference in determining the type and method of learning, class management, handling students according to their needs and conditions, measuring learning achievement , and in the end, to evaluate and follow-up the results. The proper application of psychology in the world of education is expected to help improve the quality and the output so that educational goals are achieved as stated in the law. Good quality of education will be able to help shape the next generation, who will become leaders of the nation, to become an intelligent with noble character so as to be able to bring Indonesia back to its golden age.